Mindfulness program to prevent academic stress in Higher Education students - Farfán Bellido, René (2023)
The essential objective of the study was to determine the influence of the Mindfulness program in the prevention of academic stress in higher education students. The research used the quantitative approach of experimental type accompanied by the pre-experimental design of cause and effect. The study sample consisted of 25 students from the "José Salvador Cavero Ovalle" public Pedagogical Higher Education school, the type of sampling was non-probabilistic census type. The statistician used was determined from the Levene's test of normality, determining the use of the Wilcoxon Z Test of ranks since it was about scales and numerical variables. The results showed in the pre-test that 64% of students sometimes presented academic stress, likewise, 24% of students almost always presented academic stress; meanwhile, with the experimental treatment, 72% of the students rarely present academic stress, therefore, 20% of the students no longer present stress. It is concluded that the value of the Wilcoxon ranges of Z = -4.625 with the (bilateral) meaning obtained of 0.000, a value that is lower than the critical region α= 0.05, therefore, the null hypothesis was rejected and the alternate was accepted; With a significance level of 5% and a confidence level of 95%, the Mindfulness program had a significant influence on the prevention of academic stress in higher education students.